Research of the Effect of Factors on the Process of Separation of Shadow Seeds from the Peel - N.Z. Sharipov; F.S. Kuldosheva; J.Jumaev (Genius Journals, 2022)
The research illustrates that soybeans are a non-traditional raw material in the oil industry in Uzbekistan. To date, the country has grown 16,000 tons of soybeans. Soybeans contain 24-45% protein, 17-22% fat, 20-32% carbohydrates, 1-2% lycitin, vitamins D, B and E. The weight of 1000 pieces is 140-200 g. Soybeans from the seeds are used to make flour, oil, protein and lysine. 89-92% of soybean seeds are kernels, 6- 9% are husks and 2-2.5% are apricots. The data show that the development and creation of energy and resource-saving equipment for the processing of locally grown soybean seeds is of great importance. This article presents the results of an experimental study of the process of separating the bark of the locally grown variety "Universal". Mathematical planning of the experiment was performed. An experimental device has been developed. Experiments were conducted. As a result of mathematical and statistical processing of experimental results, a generalized empirical equation of the separation coefficient was obtained: the angle of inclination of the blade, the initial moisture of the seeds, the speed of rotation of the drum, the speed of air flow, the initial consumption of the product. The generalized empirical equation obtained is used to determine the optimal processing methods for separating the local soybean seed from the husk.
Keywords: local shadow; factors; knife; drum